A 55 year old man with progressive neurologic deficits - Muljadi, Sendjaja; Senjaya, Hardy (Universa Medicina, 2009)
At least 50 percent of the decline in functional abilities associated with the elderly is caused by neurological conditions, particularly vascular dementia, such as occurs in Binswanger disease. Binswanger disease is a rare condition, characterized by acute strokes with symptoms and signs compatible with lacunar infarction. The disease onset is commonly between 55 and 75 years. The majority of patients with Binswanger disease have chronic hypertension and other putative factors including diabetes mellitus, polycythemia, thrombocytosis, hyperlipidemia, hyperglobulinemia and pseudoxanthoma elasticum, increased fibrinogen levels and the antiphospholipid antibody syndrome. We report the case of a 55 year-old man, who suffered from involuntary movements of his right arm, slight hemiparesis on the right side, and also had dementia. He had a history of high blood pressure and laboratory tests showed that he had diabetes mellitus. The brain magnetic resonance imaging showed irregular white matter abnormalities with multiple lacunar infarcts in the basal ganglia and pons. The clinical picture is characterized by acute strokes, followed by involuntary movements and also dementia. Therefore we decided to diagnose it as Binswanger disease. After discharge from hospital, the patient has not returned for follow-up.